DEVELOPMENT OF MESOPOROUS SILICA NANOPARTICLES (MSN) AS DRUG DELIVERY SYSTEMS WITH PH-RESPONSIVE GATEKEEPER CONTAINING CELECOXIB AND IN VITRO ANTI-INFLAMMATORY POTENTIAL ACTIVITY - Faraz Zefrina, Normalita
Background and purpose: Development of drug delivery systems has been a pivotal area in nanomedicine, addressing challenges such as uncontrolled release of drug loading. This study aims to develop and evaluate functionalized mesoporous silica nanoparticles (MSN) for delivery systems of celecoxib, enhancing drug loading capacity, achieving controlled release, and improving celecoxib delivery in macrophage cells (RAW 264.7) through polyethyleneimine (PEI) and imidazolyl polyethyleneimine (IP) gatekeepers. Methods: MSNs were synthesized using cetyltrimethylammonium bromide (CTAB) as surfactant template and tetraethyl orthosilicate (TEOS) as silica source, then functionalized with (3-aminopropyl) triethoxysilane (APTES) to create amine-grafted MSN (MSN-NH2). Celecoxib was loaded into MSN-NH2, followed by further modification using succinic anhydride to form MSN-NH2-Cxb-COOH, which serves as a binding site for the conjugation of gatekeepers PEI (MSN-Cxb-PEI) and IP (MSN-Cxb-IP) onto the MSN surface. This conjugation was synthesized via amide reaction. Characterization of MSN and its modifications was conducted using FTIR, TGA, DLS, and nitrogen adsorption. The successful synthesis of IP was confirmed by FTIR and 1 H-NMR. Drug loading capacity, entrapment efficiency, and in vitro drug release at pH 5.5 and 7.4 were evaluated. Cytotoxicity was assessed using MTT assay on RAW 264.7 cells. The nitric oxide (NO) inhibition assay was performed using Griess reagent on RAW 264.7 cells stimulated with LPS (lipopolysaccharides) and treated with formulations. Results: Amine-grafted MSN demonstrated a celecoxib loading capacity of 22.26 ± 1.18%, which is 3 times higher than non-functionalized MSN. In vitro release studies showed pH-responsive behavior with significantly higher celecoxib release from MSN-Cxb-IP at pH 5.5 compared to pH 7.4, achieving a 33% increase in release rate within 2 hours. Cytotoxicity assay indicated significantly higher cell viability for IP-treated cells compared to PEI-treated cells, confirming IP modification reduces PEI toxicity on RAW 264.7 cells. MSN modification with PEI and imidazolyl PEI gatekeepers provides controlled pHresponsive drug release. Formulation of MSN-Cxb-IP at low doses significantly inhibits nitric oxide production on RAW 264.7 cells (17.64%) compared to other formulations. Conclusion: These findings highlight the potential of MSN-Cxb-IP formulation as a controlled drug delivery system for inflammatory therapies.